Solution of a Transportation Problem using Bipartite Graph (Global Journal of Science Frontier Research, 2021)
The transportation problem is also one of the important problems in the field of optimization in which the goal is to minimize the total transportation cost of distributing to a specific number of sources to a specific number of destinations. Different techniques have been developed in the literature for solving the transportation problem. Specific methodologies concentrated on finding an initial basic feasible solution and the other to find the optimal solution. This manuscript analyses method of the optimal solution for the transportation problem utilizing a Bipartite graph. This procedure contains topological spaces, graphs, and transportation problems. Initially, it converts the transportation problem into a graphical demonstration then transforms into a new graphical image. Afterward using the proposed algorithmic rule we've obtained the optimal cost of transporting quantities from providing vertices to supply vertices.
Keywords: transportation problem; bipartite graph; balanced and unbalanced; VAM and MODI methods